The dynamic modelling of a laboratory-scale packed distillation column, used to separate mixtures of tetrafluoroethylene, hexafluoropropylene and octafluorocyclobutane at sub-zero temperatures - Sonnendecker, Paul Walter (University of Pretoria, 2020)
Dissertation (MEng)--University of Pretoria, 2019.